Development of Interactive Learning Media Based on Articulate Storyline 3 Theme 5 My Heroes on Student Learning Interest Grade IV Elementary School - Nisa Azkiah Simatupang; Safrida Napitupulu (PT Inovasi Pratama Internasional, 2023)
This study aims to develop media based on Articulate Storyline 3 on Theme 5 My Heroes, determine the feasibility and interest of grade IV students at SD Negeri 115486 Ujung Padang. This research is a type of development research (Research and Development) using the ADDIE development model which includes five stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were media design expert validators, material experts, learning experts (teachers) and grade IV elementary school students. The instrument used to collect data is a questionnaire. The data analysis technique used in this research is descriptive qualitative and descriptive quantitative. Based on data analysis obtained through the validity test of material experts, media design experts, teacher responses, and student responses. The results of validation by material experts are 72% including the valid / good category. The results of validation by media design experts are 66% including the valid / good category. The validation results of the fourth grade teacher's response were 72.5% including a very valid / good category, while for student responses, 85% included a very valid / good category. Based on the percentage results from material experts, media design experts, teacher responses and student responses, then calculated the average results obtained 86.2% including in the category very good / very feasible to use in the learning process. Based on the feasibility of media from the input of material experts, namely lecturers, media experts, namely lecturers and learning experts, namely the response of grade IV teachers, as well as student responses to learning media. From the data from the validation results, the development of Articulate Storyline media material on the Struggle of Heroes developed by researchers is declared very feasible to use as teaching materials in the learning process.